2020
DOI: 10.4148/1944-9771.1237
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Experiences of Familiar Identity Theft Victims When a Parent is the Perpetrator: A Pilot Study

Abstract: Incidents of familiar identity theft are becoming more common, yet limited research has explored the experiences of such victims, particularly those who had their identity stolen by a parent. In this qualitative pilot study, six participants shared their experiences during interviews. Data were analyzed using interpretive content analysis. The following preliminary themes emerged from the data: Not Filing a Police Report, Negative Impacts, Positive Impacts, Social and Demographic Factors, and Helpful Resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although few prior studies examine the characteristics of child identity crime perpetrators, the available evidence indicates that some child victims experience familiar identity crime (i.e., identity theft and/or fraud perpetrated by a family member or close associate of the victim; Betz-Hamilton, 2020). Nearly three-quarters of the respondents who participated in Javelin's Child Identity Fraud survey indicated that victimized children personally knew their identity crime perpetrator(s) (Kitten et al, 2021).…”
Section: Impact Of Child Victimizationmentioning
confidence: 99%
“…Although few prior studies examine the characteristics of child identity crime perpetrators, the available evidence indicates that some child victims experience familiar identity crime (i.e., identity theft and/or fraud perpetrated by a family member or close associate of the victim; Betz-Hamilton, 2020). Nearly three-quarters of the respondents who participated in Javelin's Child Identity Fraud survey indicated that victimized children personally knew their identity crime perpetrator(s) (Kitten et al, 2021).…”
Section: Impact Of Child Victimizationmentioning
confidence: 99%
“…Golladay (2017) found victims who did not know the offender were 77% less likely to file a report with a law enforcement agency. This suggests familiar identity theft offenders may be more likely to report to a law enforcement agency, but this was not the case in a qualitative study of victims who had their identity stolen by a parent (Betz-Hamilton, 2020b). Other factors found to influence victims’ decision to report to law enforcement were being a minority and experiencing identity theft (Golladay, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From 2019 to 2020, 47% of US residents experienced financial identity theft, which involved the misuse of existing financial accounts or the fraudulent creation of new accounts (Inscoe, 2021). At least half of victims who had their existing account misused knew the offender, in a phenomenon known as familiar identity theft (Betz-Hamilton, 2020b). Familiar identity theft offenders can be family members of the victim as well as associates such as neighbors, coworkers and school staff.…”
Section: Introductionmentioning
confidence: 99%